Green Accounting as a Mediation Variable, and Media Exposure as a Moderation Variable in the Relationship Between Profitability and CSR Disclosure - Mardalena Septi Mi Darti; Nurna Aziza (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to analyze Green Accounting as a mediation variable, and Media Exposure as a moderation variable in the relationship between profitability and CSR Disclosure in LQ45 companies in 2018-2022. This study used the population of LQ 45 companies listed on the Indonesia Stock Exchange during the period 2018-2022. The data used is secondary data in the form of annual financial statements and sustainability reports. The sample consisted of 20 companies that met the criteria during 2018-2022 as many as 100 samples. The data analysis used is a statistical analysis method with a path analysis model (Path Analysis). The results of the analysis show that there is no effect of profitability on CSR disclosure. There is no effect of profitability on green accounting. Profitability through green accounting has a significant effect on CSR disclosure. Green accounting mediated by media exposure has a significant effect on CSR disclosure.